2015
DOI: 10.1111/nan.12294
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Lewy bodies and Aβ burden are associated with prevalence and timing of dementia in Lewy body diseases

Abstract: Results:The cortical LB (CLB) burden was the only independent predictor of dementia (OR: 4.12, p<0.001). The total cortical Aβ plaque burden was an independent predictor of a shorter latency to dementia from onset of motor signs (p=0.001). DLB cases had a higher LB burden in the parietal and temporal cortex, compared to PDD. Carrying at least one APOE ϵ4 allele was associated with a higher cortical LB burden (p=0.02), particularly in the neocortical frontal, parietal, and temporal regions. Conclusions:High CLB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
90
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 66 publications
8
90
2
Order By: Relevance
“…7 However, additional research has reported that Aβ plaques 8,20 or a summation of NFT, Aβ, and SYN pathological changes 21 were the strongest correlates of a shorter MDI in LBSD. There are several potential reasons for these discrepancies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…7 However, additional research has reported that Aβ plaques 8,20 or a summation of NFT, Aβ, and SYN pathological changes 21 were the strongest correlates of a shorter MDI in LBSD. There are several potential reasons for these discrepancies.…”
Section: Discussionmentioning
confidence: 96%
“…However, our multi-center cohort is one of the largest reported series of clinically-characterized patients with roughly equal numbers of PDD and DLB patients which allowed for comparisons across four levels of Braak/CERAD scores and a continuous measure of average cerebral NFT/NP scores. In contrast, previous studies had limited evaluations of NFT pathology by collapsing Braak stages for dichotomous comparisons 8 or by examining categorical Braak NFT stages only 20 in smaller samples with relative imbalances of PDD/DLB 20,21 or only non-demented PD or PDD 8 . Although in this study we focused on LBSD patients who developed dementia (PDD/DLB) and did not examine PD patients who came to autopsy prior to the onset of dementia (PDND), we have previously published a series of autopsy-confirmed PDND patients 6 and found the majority of cases had a low level of tau pathology—35/44 (79%) of cases had low Braak tau stages=0–II (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Although α-synuclein deposition in Lewy bodies is the core neuropathologic feature of the LBD, tau and Aβ co-pathologies are commonly observed in most patients with DLB and PDD at autopsy (26). Supporting their contribution to cognitive function in these diseases, neuropathological studies of DLB and PDD have tied both tau and Aβ to severity of dementia (35).…”
Section: Discussionmentioning
confidence: 99%
“…In individuals with DLB and PDD, co-existent Alzheimer’s disease (AD) pathology, in the form of extracellular amyloid plaques and intracellular paired helical filaments of tau, is commonly observed at autopsy (26). The relevance of these protein aggregates to the course of these diseases has been based primarily on clinico-pathological correlations.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, DLB and PDD cases were grouped together as one Lewy body dementia cohort to investigate effects of antidepressant treatment on neurogenesis and cognition. Whilst the 1-year rule is still routinely clinically applied to differentiate between the two dementia forms, several studies have suggested differences in amyloid load and Lewy body cortical load [47,48,49,50,51] which could also have an impact on the rate of neurogenesis. It would, therefore, be of interest to take this into consideration in future studies investigating neurogenesis in DLB/PDD.…”
Section: Discussionmentioning
confidence: 99%